Inovasi Pelayanan Kependudukan Berbasis Braille di Kota Malang - Setiawan, M N Romi A; Dewi, Dewa Ayu Putu Shandra; Helda, Maria Elfrida Nona (Indonesian Social Science Review, 2023)
This research aims to determine the service innovation "Braille Dukcapil Administration (Ouch Bra)" for people with disabilities at the Malang City Civil Registration Population Service. Braille Dukcapil Administration ("Aduh Bra" is an innovative form of braille population document as a breakthrough in realizing a disability-friendly Malang City. Through this innovation, Malang City residents with special needs, especially people with disabilities, can independently read and understand their population documents. UU -The law on persons with disabilities is a form of government concern as a guarantee for people with disabilities. The problem is innovating the "Braille Dukcapil Administration (Ouch Bra)" service for people with disabilities at the Malang City Civil Registration Population Service. This research method uses a qualitative descriptive method. The data sources collected in this research are primary and secondary data. The data collection techniques used are interviews, observation, and documentation. The technique for determining informants is snowball sampling. The data analysis techniques in this research are data collection, data reduction, presenting data, and drawing conclusions. This research shows that the Service Innovation "Braille Dukcapil Administration (Ouch Bra)" for Persons with Disabilities at the Malang City Civil Registration Population Service is seen from the benefits, suitability, complexity, and possibility of trying it. Meanwhile, the supporting factors are the Cooperation Agreement (PKS) between the population and social services. Meanwhile, the inhibiting factor is human resources, who have more dedication to serving with a high level of difficulty. Penelitian ini bertujuan untuk mengetahui Inovasi Pelayanan “Administrasi Dukcapil Huruf Braille (Aduh Bra)” Bagi Penyandang Disabilitas Pada Dinas Kependudukan Pencatatan Sipil Kota Malang. Administrasi Dukcapil Huruf Braille (“Aduh Bra” adalah bentuk inovasi dokumen kependudukan berhuruf braille ini sebagai bentuk terobosan akan perwujudan Kota Malang yang ramah disabilitas. Melalui inovasi ini warga Kota Malang yang berkebutuhan khusus terutama kaum disabilitas dapat membaca dan memahami dokumen kependudukannya secara mandiri. Undang-undang penyandang disabilitas merupakan salah satu bentuk kepedulian pemerintah sebagai jaminan kepada masyarakat yang memiliki kelainan disabilitas. Masalah yang mengenai bagaimana Inovasi Pelayanan “Administrasi Dukcapil Huruf Braille (Aduh Bra)” Bagi Penyandang Disabilitas Pada Dinas Kependudukan Pencatatan Sipil Kota Malang. Metode penelitian ini menggunakan metode deskriptif kualitatif. Sumber data yang dikumpulkan dalam penelitian ini adalah berupa data primer dan sekunder. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan dokumentasi. Teknik penentuan informan adalah snowball sampling. Teknik analisis data dalam penelitian ini yaitu pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian penelitia ini menunjukan bahwa Inovasi Pelayanan “Administrasi Dukcapil Huruf Braille (Aduh Bra)” Bagi Penyandang Disabilitas Pada Dinas Kependudukan Pencatatan Sipil Kota Malang yaitu dilihat dari keuntungan, kesesuaian, kerumitan, dan kemungkinan dicoba. Sedangkan untuk factor pendukung perjanjian Kerjasama (PKS) antara dinas kependudukan dan dinas sosial. Sedangkan factor penghambat yaitu dari sumber daya manusi yang memiliki dedikasi lebih dalam melayani dengan tingkat kesulitan yang tinggi.